Understanding physical activity declines during COVID-19: The affective repercussions of disruption to exercise routines. (January 2023) - Furman, Celina R.; Volz, Sarah C.; Rothman, Alexander J.
Abstract: Recent research has examined psychological factors that forestalled declines in physical activity (PA) during the early stages of the COVID-19 pandemic. Surprisingly, there has been limited evidence of an association between intrinsic motivation (IM) and PA. We reasoned that IM may have not predicted PA because COVID-19 restrictions limited opportunities to engage in exercise in ways that produced positive affective experiences (i.e., inherent rewards). Using data from a cross-sectional survey ( N  = 373 participants), we tested a moderated mediation model that predicted perceived changes to affective experiences during exercise would mediate the association between disruption to one's exercise routine and self-reported declines in PA, and that effects would be moderated by IM. Evidence of moderated mediation was found, suggesting that disruptions to exercise routines were associated with fewer positive affective experiences during exercise that predicted declines in PA engagement, especially for people who typically exercised for intrinsic reasons. Highlights: Disruption to exercise routines was associated with perceived MVPA declines. People experienced less positive and more negative affect during exercise. Affective changes partially mediated association between disruption and MVPA. Intrinsic motivation moderated positive affect pathway.